(untitled) (Linguostylistic Studies, 2015)
The article offers an analysis of prose microcontext with graphic elements of heterogeneity. The formal syntactic, structural and semantic, structural and compositional heterogeneity of graphical tools are differentiated in one of the novels of Maria Matios, underline their role in the formation of the narrative, the story works organization and its composition. The game graphic images are qualified as a stylistic device in the narrative structure of postmodern works. The peculiarity of the use of capital letters in the selection of the author’s modality. n this regard, analyzed microcontext where graphic heterogeneity of contributes to the alignment of certain stylistic evaluation, psychological emphasis in the process of unfolding storyline and alignment of the text composition, providing the basic idea of the work. Key words: narrative, the author’s modality, a stylistic device, graphic heterogeneity of of the text, graphic style of the text. References